STRATEGI PENGENDALIAN TUBERKULOSIS DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Ria Yayanti; Ridwan Manda Putra; Bayhakki Bayhakki (Pelantar Press, 2025)
Tuberculosis (TB) remains a major health problem in Indonesia, with Pekanbaru City—particularly Marpoyan Damai Subdistrict—recording the highest number of cases (1,558). This study aimed to formulate evidence-based strategies to sustainably reduce TB incidence and transmission. A descriptive quantitative approach was applied using primary and secondary data collected through questionnaires, field observations, and documentation. A total of 91 respondents were selected by simple random sampling from 1,558 TB households. Data were analyzed descriptively and through SWOT analysis. Findings indicated an increasing TB trend, from 1,200 cases in 2020 to 1,650 in 2024, including a rise in pediatric TB. Risk factors included poor ventilation and lighting (40.7%), smoking habits (50.5%), low mask use, and high household density. SWOT analysis revealed IFAS = 0.67 and EFAS = 1.10, placing the strategy in Quadrant I (aggressive). Recommended strategies include community education, optimizing the role of health cadres, maximizing healthcare facilities, improving housing environments, and strengthening cross-sectoral collaboration to accelerate TB control